Sistem Kerja Organisasi Mradio Dalam Meningkatkan Efektivitas Kerja Demi Mencapai Tujuan Bersama - Amanda Zafira Wijaya; Dinda Nuraini; Zakiyyah Tsurayya Salim; Farhan Yut Wijaya; Jamiati Jamiati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Mradio is a radio community under the auspices of the Faculty of Social and Political Sciences, Muhammadiyah University, Jakarta, which aims to be a forum for students to deepen their skills in the field of broadcasting. There is a work system within Mradio which was deliberately created to improve performance and reduce the possibility of repeating errors for each member within it, where a clearer and neater work flow can be created, so that work effectiveness can be established there. The bureaucratic system is used to achieve work effectiveness at radio because it makes communication more structured by relying on multilevel levels starting from the head of management to members of each departementon. This research aims to determine the organizational performance system of Mradio, as well as to determine whether or not there is an influence of the organizational work system on the performance of Mradio members. The approach used in this research uses a qualitative approach which emphasizes the meaning, reasoning, definition of a particular situation. The type of research method used in this research is the descriptive method.